Selective red-emission detection for mercuric ions in aqueous solution and cells using a fluorescent probe based on an unnatural peptide receptor. Issue 14 (25th March 2019) - Neupane, Lok Nath; Mehta, Pramod Kumar; Kwon, Joon-Uk; Park, See-Hyoung; Lee, Keun-Hyeung
Abstract : The selective ratiometric red-emission detection of Hg 2+ ions in aqueous buffered solutions and live cells is still a significant challenge. Abstract : The selective ratiometric red-emission detection of Hg 2+ ions in aqueous buffered solutions and live cells is still a significant challenge. In the present study, we synthesized a fluorescent probe (1 ) based on an unnatural peptide receptor containing sulfonamide groups with an aggregation-induced emission and twisted internal charge transfer (TICT)-active fluorophore, cyanostilbene.1 exhibited a highly selective ratiometric response to Hg 2+ among 14 metal ions tested by ratiometric red-emission at 600 nm, with a clear isoemissive point in purely aqueous solution containing 1% DMSO. The ratiometric response for Hg 2+ ions was complete within 3 min and the ratiometric responses induced by Hg 2+ ions did not suffer considerable interference from the other metal ions. The ratiometric response was complete for less than 7 μM Hg 2+ and1 had a potent binding affinity (7.42 × 10 −6 M, R 2 = 0.98) for Hg 2+ and a nanomolar detection limit.1 detected Hg 2+ ions by ratiometric responses in aqueous buffered solutions over a wide range of pH (5.5–11.5). Binding mode studies using TEM, NMR, IR, and a mass spectrometer revealed that the sulfonamide groups of the unnatural peptide receptor played an important role in the complexation of Hg 2+ and in the complexation-induced nano-sized aggregates, which resulted in a significant increase in emissions at 600 nm and a decrease in emissions at 535 nm.1 quantified micro-molar concentrations (0–6 μM) of Hg 2+ in tap water and groundwater by ratiometric detection. Furthermore, 1 passed through the lipid membranes of live cells and detected intracellular Hg 2+ ions at 2 μM by a ratiometric red-emission change.